Maternal and Neonatal Outcomes in Women with Preeclampsia - Mandana Saadat; Soheila Marzoughian Nejad; Gholamreza Habibi; Mehrdad Sheikhvatan (Elsevier, 2007)
Objective: Preeclampsia is a pregnancy-specific hypertensive syndrome associated with significant morbidity and mortality in mother and neonate. We compared neonatal and maternal complications in preeclamptic women with healthy pregnant women. Materials and Methods: All 125 consecutive women with preeclampsia at Bandarabbas Shariati Hospital were assessed between July 2005 and July 2006. Parity, type of delivery, common causes of cesarean section, gestational age, birth weight, and neonatal complications and mortality were included as study variables and compared with the control group. Results: Cesarean section rates were significantly higher in the group with preeclampsia than in the control group (p < 0.05). The mean parity was higher in the normotensive group than in the preeclamptic patients (2.3± 0.65 vs. 3.6± 0.74; p < 0.05). In the preeclamptic women undergoing vaginal delivery, 31% of them underwent induction of labor. The most common indication for induction of labor was severity of preeclampsia (77.8%). Birth weight was statistically significantly lower in women with preeclampsia (p < 0.0001). Among the patients, 5.6% of them were admitted with intrauterine fetal demise, while 111 neonates survived for the remaining patients. The most common causes of neonatal mortality were congenital abnormalities and respiratory distress syndrome. Conclusion: Gestational age, parity, cesarean section rate, the rate of induced labor, and low birth weight neonates were more frequent in preeclamptic women than in healthy pregnant women.